The Contribution of Muhammadiyah in Fostering Social Harmonization through a Wasathiyah Approach in a Multicultural Society - Fauzia Fauzia; Yasir Marzuqi; Amrullah Amrullah (Universitas Nurul Jadid, 2026)
This study aims to analyze the contribution of Muhammadiyah in fostering social harmonization within a multicultural society through the implementation of the wasathiyah (religious moderation) approach. The research was conducted in Muhammadiyah-affiliated educational institutions and surrounding communities in Indonesia, particularly in areas characterized by cultural, religious, and social diversity. This study employed a qualitative research design using a case study approach. Data were collected through in-depth interviews with educators and community leaders, direct observations of educational and social activities, and analysis of institutional documents. The data were then analyzed using thematic analysis to identify patterns and meanings related to the application of wasathiyah values. The findings indicate that Muhammadiyah plays a strategic role in promoting social harmony through inclusive education practices, transformative and enlightening da’wah, community-based social services, and active participation in national and civic engagement. The wasathiyah approach is manifested in the integration of religious commitment, humanitarian values, and national identity, which contributes to reducing potential social conflicts and strengthening mutual respect among diverse groups. Additionally, this study finds the development of a contextual learning model in Muhammadiyah schools that systematically incorporates moderation values into both curriculum and daily practices. In conclusion, Muhammadiyah serves not only as a religious and educational organization but also as an agent of peace that significantly contributes to building and sustaining social harmonization in Indonesia’s multicultural society.